Fungsi Pengawasan Dalam Meningkatkan Disiplin Kerja Pegawai (Suatu Studi Di Kantor Camat Sario) - Sumual, Meytha Margaretha; Ogotan, Martha; Sampe, Stefanus (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT :This study aims to determine whether the implementation of the supervisory function bycamat are being implemented properly and effectively so as to improve the discipline of employees workingat the district office Sario. This oversight also diamksudkan that the goals and objectives of businessactivities of governmental units can be achieved efficiently (efficient) and effective (effective), carried outin accordance with the basic tasks, functions, plan or program, the division and delegation of tasks, theformulation of the work, guidance implementation and legislation that berlaku.dengan good and effectivesupervision cultivated avoid deviations implementation, abuse of authority, leakage and wastage.Methods, research used in this study is a qualitative method, with the techniques of collecting primary andsecondary data were collected by interview, documentation and observation studies. As an advancedrespondent / informant of this study was Head Sario (key informants), Secretary of the Head and 3 of SectionHead (key informants), 2 staff of the District (informant extra), District Sario consists of 7 Village are:Village Sario New Town , South Titiwungen Village, Village North Titiwungen, Village Sario, SarioTumpaan Village, Village North and sub Ranotana Sario.The results showed that the monitoring of the Civil Service Head Office Sario who commits an offenseagainst the discipline of working hours it is already running, but not too maximum punishment provisionunder the rules of Regulation No. 53 In 2010, the application of penalties based on the achievement of theobjectives of employee has been running for some employees in carrying out the task set was still gettingguidance from superiors in carrying out its performance. Based on the interview can be concluded that theimposition of sanctions in the District Office Sario in accordance with the disciplinary rules of civil servantsand procedures for application of punishment or imposition of disciplinary sanctions in accordance withGovernment Regulation No. 53 Year 2010 which sanctions carried out in accordance with the level ofviolations committed by employees who abuse and still coordinate with the inspection team if the offense isat a level of moderate and severe disciplinary action.Referring to the discussion and conclusions on the proposed recommendation in this study are as follows:Application monitoring should be done more leverage, so that the utilization of the working time ofemployees will be more effective and efficient, along with its implementing regulations are strict and fair,need of socialization of Government Regulation No. , 53 of 2010 on Discipline of Civil Servants to allemployees at the Head Office Sario to be more aware of the rules of obligations and prohibitions andsanctions that would be acceptable if it violates these rules, supervision of direct supervisor should bemaximized so that the Civil Service to understand the actual legal and output which is expected in the processof enforcement of penalties. So there is no indifference / not stated if there are other Civil Servants in theworkplace that disciplinary offenses.Keywords: Increasing Discipline Oversight Functions In Employee Work.